THE DIDACTIC CARD GAME "PEDAGOGY IN PHYSICAL EDUCATION - CAREFULLY AND QUICKLY" - Remus-Cristian VĂIDĂHĂZAN; Cosmin PRODEA (Cluj University Press, 2015)
Teaching methods are continuously developed. New methods may appear periodically through the combination of existing ones, adjusted by the experience of teachers. The most effective, in our opinion, are those that help us achieve educational objectives without neglecting students' motivation for proposed tasks. After the success we had with the didactic card game "Didactireka" (Văidăhăzan & Prodea, 2012) we continued to experience such changes in our collection of teaching methods. The idea for this didactic card game came from the card game "Jungle Speed" that we found on the internet. In this article we describe how we transformed the card game "Jungle Speed" into educational card game "Pedagogical concepts in Physical Education - carefully and quickly". The game we created has 168 cards, of which 144 are playing cards and 24 are action cards, plus a "treasure". The best dynamic of the game we had with five teams (with 3 or 4 players on the team) or six teams (2 or 3 players on the team). The game can take place on two levels of difficulty. The first difficulty level is to not take into account pedagogical concepts related to words on the playing cards. The second difficulty level requires players that win a duel to define the concept typed on the playing cards included in a duel. If he/she fails to do so then the game continues without winning that duel.